MEMAHAMI DAN MENGANALISIS MANAJEMEN KESISWAAN DI MTSN 1 BUKITTINGGI - Emeliazola (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is motivated by the success of an educational institution in achieving its intended goals will never be separated from the management system within it. Where educational management is the process of planning, organizing, directing and controlling personal educational efforts to utilize all resources in order to achieve educational goals. The aim of this research is to understand and analyze student management. The research method is literature study and observation. The results of the MTsN 1 Bukittinggi student management research, starting from analyzing the needs of students, have carried out their duties in holding meetings and determining the number of students, which have been carried out, the recruitment of students, head of student affairs and the head of the sub-division of committee participants have carried out their duties in admissions. new students have been implemented, then the placement of students has been carried out well, but there is one thing that has not been implemented because the head of student affairs and the principal do not allow students to choose their friends at will, and the coaching and development of students has been carried out but sometimes it has not been implemented because of the It's planned and sometimes it doesn't work out.